2014
DOI: 10.1097/brs.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Discogenic Back Pain

Abstract: Study Design Systematic review of the literature. Objective A systematic evaluation of the literature was performed to investigate current non-operative management for the treatment of discogenic low back pain. Summary of Background data Back pain is a major healthcare concern with up to 39% being discogenic in origin according to one study. Non-operative therapy is likely to be the initial treatment strategy for discogenic low back pain. Methods Pubmed, Embase and Cochrane Central Register of Controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 59 publications
0
45
0
1
Order By: Relevance
“…This is a crude publication rate of 1.5 articles per year, which does not seem considerably different from other areas of prosthetics and rehabilitation. Examples include a recent review of microprocessor knees that yielded 18 articles in a 14 yr review period (crude rate of 1.3 articles/year) [45] or spinal rehabilitation that yielded 11 randomized trials in a 13 yr review period (0.8 trials per year) [46]. The difference is that the reviews on microprocessor knees and spinal rehabilitation were reviewing only very specific studies (i.e., comparative effectiveness only), whereas this review included all [37] O5 Meredith (1994) [38] O5 N/A N/A      Low         High Berbrayer and Farraday (1994) [39] study design types as well as editorials.…”
Section: Discussionmentioning
confidence: 99%
“…This is a crude publication rate of 1.5 articles per year, which does not seem considerably different from other areas of prosthetics and rehabilitation. Examples include a recent review of microprocessor knees that yielded 18 articles in a 14 yr review period (crude rate of 1.3 articles/year) [45] or spinal rehabilitation that yielded 11 randomized trials in a 13 yr review period (0.8 trials per year) [46]. The difference is that the reviews on microprocessor knees and spinal rehabilitation were reviewing only very specific studies (i.e., comparative effectiveness only), whereas this review included all [37] O5 Meredith (1994) [38] O5 N/A N/A      Low         High Berbrayer and Farraday (1994) [39] study design types as well as editorials.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review on non‐operative management for discogenic back pain Lu et al. (2014) mention the study from Oh and Shim (2004) as the only one targeting the ramus communicans. The RF treatment used in this study was the same as in our study; however, patients were eligible for this RCT only when their pain continued after intradiscal electrothermal annuloplasty (IDET).…”
Section: Discussionmentioning
confidence: 99%
“…119 The evidence supporting other treatments for discogenic pain, including epidural and intradiscal injections, and thermal ablation, is weak and inconsistent. [120][121][122][123][124] Neuropathic pain Cervical disc herniation The annual incidence of cervical radiculopathy resulting from disc protrusion or degenerative spondylosis (or both) is estimated at 1-3.5 per 1000 person years, peaking in the sixth decade of life. A population based study reported a 0.055% incidence of radicular pain secondary to a cervical herniated disc, although estimates based on patients seeking medical attention underestimate incidence.…”
Section: Myofascial Painmentioning
confidence: 99%
“…124 135 Comparative effectiveness studies by one group showed similar benefit in pain relief, function, and other outcome measures such as opioid consumption and employment for both steroids and local anesthetic in a variety of cervical diseases including disc hernation. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] Another randomized study in 169 patients with radicular pain found the combination of ESI and conservative treatment consisting of physical therapy and the adjuvants nortriptyline or gabapentin (or both) provided superior relief compared with either treatment alone (mean reduction in pain score of 3.1 in the combination group versus 1.9 in the others at one month; P=0.035). 139 Together, these studies provide limited evidence that ESI is more effective than epidural non-steroid injections but moderate evidence that a series of epidural injections can provide sustained relief.…”
Section: Cervical Discogenic Painmentioning
confidence: 99%